(untitled) (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Applications are made for inventory optimization case study CV.ASAKU using safety stock, EOQ, moving average and exponential smoothing. The case study used is CV.ASAKU, CV.ASAKU engaged in paper and pulp in cooperation with Sinarmas paper and pulp. The purpose of this system is to help optimizing inventory in CV.ASAKU with various obstacles. The method used is safety stock, forecast and EOQ. Safety stock method is used to keep inventory in order not to run out at the warehouse, judging from the sale of each item that already exists. Forecast method using three methods: the method of moving average, a double moving average and smoothing exponetial. This method is used to predict sales for the coming months and predicted results are used for calculation of EOQ method. EOQ method used to calculate the amount of each item to be purchased at the purchase time period is calculated from the cost of shipment and storage of goods in warehouses, this method serves to reduce the cost of ordering goods and storage of goods. From the three methods produce estimates of inventory at CV.ASAKU.